PEMBELAJARAN BAHASA INDONESIA ONLINE DI SEKOLAH DASAR (MADRASAH IBTIDA’IYAH) PADA TEKS INSTRUKSI PADA PANDEMI COVID-19 - Muhammad Alfi Khoiruman (Universitas Wijaya Kusuma Surabaya, 2021)
The purpose of this study is to describe scenarios of online learning carried out by teachers during the COVID-19 pandemic in instructional text learning, Difficulties experienced by students and teachers when carrying out instructional text learning in a pandemic, Students and teacher responses to online learning during a pandemic in instructional text learning, and differences in students' knowledge and skills in instructional text learning in online learning. The data collection technique in this study was through online interviews. The results of the online learning research of MI Muhammadiyah 2 Banyuwangi during the COVID-19 pandemic show that: (1) The online learning scenario that the teacher does during the COVID-19 pandemic is Distance Learning and continues to make learning plants that are arranged in a simple and concise manner. main things include pre-activity, core activity and post-activity. (2) The difficulties experienced by students and teachers when carrying out instructional text learning in a pandemic are 80% in the medium category and 20% in the low category. (3) The responses of students and teachers to online learning during the COVID-19 pandemic were 20% indicating a positive response, 40% indicating a neutral response and 40% indicating a negative response. So it can be concluded that students have different knowledge and skills in learning instructional texts in online learning.